2012
DOI: 10.1080/02626667.2012.666635
|View full text |Cite
|
Sign up to set email alerts
|

Performance of flood frequency pooling analysis in a low CV context

Abstract: Pooling of flood data is widely used to provide a framework to estimate design floods by the Index Flood method. Design flood estimation with this approach involves derivation of a growth curve which shows the relationship between X T and the return period T, where X T = Q T /Q I and Q I is the index flood at the site of interest. An implicit assumption with the Index Flood procedure of pooling analysis is that the X T -T relationship is the same at all sites in a homogeneous pooling group, although this assum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 20 publications
0
14
0
Order By: Relevance
“…larger box) when N ≤ 10. In this regard, Das and Cunnane (2012) also found an effect for N < 10 on quantile error measures (considering n = 35). In general this effect is less marked for GI when γ = 0 % ( Fig.…”
Section: Sensitivity Analysesmentioning
confidence: 88%
See 1 more Smart Citation
“…larger box) when N ≤ 10. In this regard, Das and Cunnane (2012) also found an effect for N < 10 on quantile error measures (considering n = 35). In general this effect is less marked for GI when γ = 0 % ( Fig.…”
Section: Sensitivity Analysesmentioning
confidence: 88%
“…In the present study, heterogeneous regions are simulated using the heterogeneity rate γ , defined as γ = (max i (τ i ) − min i (τ i ))/τ R (e.g. Hosking and Wallis, 1997;Das and Cunnane, 2012), where τ i is the L-CV at site i with i = 1, . .…”
Section: Synthetic Regionsmentioning
confidence: 99%
“…Obviously, the quantiles estimated by RFA have smaller uncertainty than at-site based estimates as confirmed in Tables 13 and 14. However, there is a limitation of how large the return period could reliably be estimated with respect to record length. Das and Cunnane (2012) suggested that the record length of the considered site should be at least 50 years to estimate 100-year return period quantiles effectively. We assume loosely that this statement implies the factor of 2 between the record length and return period.…”
Section: Comparison Of At-site Quantile Uncertainty Between 2 Approacmentioning
confidence: 99%
“…The reliable estimation of such extreme rainfall events requires at-site long records. Das and Cunnane (2012) showed that for at-site frequency analysis, the record length at the site concerned should exceed 50 years for the estimation of 100-year flood. However, in many regions of the world, Jakarta inclusive, the scarcity and uncertainty of data remain challenged.…”
Section: Introductionmentioning
confidence: 99%
“…If homogeneity is assured then a homogeneous region (or pooling group) of stations lead to a reduction in the error of quantile estimates, relative to estimators based on single at‐site data series alone (e.g. Hosking and Wallis, ; Das and Cunnane, ).…”
Section: Introductionmentioning
confidence: 99%